Animals of Kruger National Park - Barnes, Keith (Book collections on Project MUSE., 2016)
South Africa's Kruger National Park is one of the largest and most diverse conservation areas in Africa, and a hugely popular visitor attraction. Animals of Kruger National Park is a compact and beautifully illustrated guide, and the essential companion for any safari to the region. With an eye-catching design, authoritative and accessible text and easy-to-use format, this detailed photographic guide provides information on identification, habitat, behaviour, biology and conservation for all the mammals, reptiles and frogs likely to be seen. Introductory sections provide background information on the park and its habitats, when to visit and where to go, and other practical considerations that will help to enhance your understanding, appreciation and enjoyment of the animals of this incredible region. The essential all-in-one Kruger safari companion, ideal for all visitors Unique and attractive layout, featuring 216 stunning colour photographs, 116 track (spoor) illustrations and two maps Covers 57 mammals, 17 reptiles and eight frogs Features the 'Big 5'--elephants, leopards, lions, rhinoceroses and buffalos--as well as other iconic and charismatic animals Provides key information on identification, behaviour, biology and conservation.